Palm Oil 2016 - Elias, Jaan, (SAGE Knowledge. Cases., 2017)
In 2014, the four largest palm oil trading companies signed an agreement to end deforestation, development of peat lands and exploitation of locals not only with their own operations, but also from all of their suppliers. For environmental NGOs, the Indonesian Palm Oil Pledge (as the agreement was named) represented a dramatic advance in their decades-long efforts to protect the Indonesian rainforest from further destruction.One year later the situation appeared to have reversed. Leading figures in the government of Indonesia were calling upon the companies to withdraw their pledge. And the 2015 fire season was the worst in nearly two decades, as would-be oil palm growers set fire to rainforests and peatlands to clear them for planting.